Pengaruh Struktur Modal dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening (Studi Pada Perusahaan Infrastruktur Sub Sektor Konstruksi Berat dan Teknik Sipil Terdaftar di BEI Periode 2018-2022 - Nila Cahyani; Faridhatun Faidah; Hutomo Rusdianto (Financial and Accounting Indonesian Research, 2024)
This research aims to analyze the influences: (1) capital structure influences the value of the company, (2) corporate growth influences corporate value, (3) capital structures influence profitability, (4) corporate development influences profits, (5) profitability influences company value, (6) profitability is able to mediate the influence of capital structure on the company's value, (7) profitability can mediate company growth influence on company value. The population of this study is the entire infrastructure company of the heavy construction and civil engineering sub-sector listed on the Indonesian Stock Exchange for the period 2018-2022. The samples were selected using the purposive sampling method of 18 companies. Data analysis used in this study is internal model and hypothesis testing with the help of software SmartPLS (Partial Least Squares) version 3.2.9. PLS (Partial Least Square). The results of the research showed that the capital structure had a negative and non-significant impact on the company's value, the growth of the company had a positive and insignificant effect on the value of the enterprise, the structure of the capital had an negative and significant impact on profitability, the development of a enterprise had an positive and significant effect on profitability, the profitability had an adverse and significant influence on the corporate value, profitability was able to mediate the influence of capital structures on the business' value, and profitability were capable of mediating the impact of the growth and value of an enterprise.